2000
DOI: 10.1097/00007890-200007270-00010
|View full text |Cite
|
Sign up to set email alerts
|

Conversion From Azathioprina to Mycophenolate Mofetil in Pediatric Renal Transplant Recipients With Chronic Rejection1

Abstract: Our data suggest that substituting MMF for azathioprine therapy leads to an improvement in the immunosuppression and renal function in children with on-going chronic rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
1
17
2
Order By: Relevance
“…This is in contrast to the findings in the study reported by Anguita et al [25], who studied the effect of converting azathioprine to MMF and found no change in serum creatinine levels after a mean follow up period of 8.6 months. However, Ferraris and colleagues [26] reported that converting azathioprine to MMF in eight paediatric patients with chronic renal rejection led to a significant improvement in creatinine clearance at 15 months. In the latter study the CNI dose remained unchanged.…”
Section: Renal Functionmentioning
confidence: 99%
“…This is in contrast to the findings in the study reported by Anguita et al [25], who studied the effect of converting azathioprine to MMF and found no change in serum creatinine levels after a mean follow up period of 8.6 months. However, Ferraris and colleagues [26] reported that converting azathioprine to MMF in eight paediatric patients with chronic renal rejection led to a significant improvement in creatinine clearance at 15 months. In the latter study the CNI dose remained unchanged.…”
Section: Renal Functionmentioning
confidence: 99%
“…The occurrence of chronic transplant nephropathy, associated with calcineurin inhibitor nephrotoxicity, suggests that MMF might be the most important drug on a long-term basis [4,5,6,7]. The occurrence of chronic transplant nephropathy, associated with calcineurin inhibitor nephrotoxicity, suggests that MMF might be the most important drug on a long-term basis [4,5,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Only two patients developed rejection episodes (17). Ferraris et al (18) evaluated replacing azathioprine with MMF in 22 pediatric renal transplant recipients. Creatinine clearance increased from 44 to 51 mL/min/1.73 m 2 (p < 0.03) without significant rejection, suggesting that substitution of MMF for azathioprine was effective and improved renal function.…”
Section: Adverse Effects Of Immunosuppressionmentioning
confidence: 99%